Transcriptomics uncover inhibition of repair and wound healing pathways in Atlantic halibut (Hippoglossus hippoglossus) after crude oil exposure - Elin Sørhus; Kai K. Lie; Sonnich Meier; Tomasz Furmanek; Birgitta Norberg; Prescilla Perrichon (Ecotoxicology and Environmental Safety)
Accidental oil spills significantly threaten marine ecosystems and fisheries, impacting biodiversity and ecological health. This study examines the downstream transcriptomic responses of Atlantic halibut larvae exposed to crude oil during organogenesis. Findings show concentration-dependent transcriptional abnormalities. Pathway analysis at 10 days post-hatch (dph), 11 days after cessation of oil exposure, indicates downregulation of inflammatory and reparative pathways. By 18 dph, tissue-specific analyses reveal activation of these pathways, especially in head tissues, alongside upregulation of neuronal signaling pathways. This highlights the complex relationship between oil exposure and transcriptional responses, emphasizing recovery mechanisms represented by regulation of inflammatory, repair and wound healing pathways following oil exposure. The activation of repair pathways in surviving larvae suggests compensatory processes to address oil-induced damage. These novel insights enhance understanding of the molecular mechanisms of oil toxicity and the lasting effects on marine organisms.